A Case Study of Local Community Development and Citizen Participation in Cuba: A Comprehensive Neighbourhood Transformation Approach. (1st April 2019) - Bonilla-Santiago, Gloria
Abstract : The comprehensive neighbourhood transformation approach of planning in the Havana Historian's Office is a case study of local community development in the capital of Cuba. The study is justified by its relevance and timeliness of the issues found in community development and its implications in people and place wellbeing, especially in the most disadvantaged sectors of Cuban society. It seeks to analyse the improvement of life conditions in achieving social inclusion, citizen participation in community. A theoretical analysis of community development and local development within a community capital approach is provided. The experiences of the comprehensive neighbourhood transformation workshops constitute an important contribution to the local/community development process. The use of endogenous resources for managing human, social, political, natural and cultural capital ensures sustainable community development and innovative methodologies for community planning.